Pequenos trabalhadores: infância e industrialização em Caxias do Sul (fim do Séc. XIX e início do Séc. XX) - Tisott, Ramon Victor (Universidade do Vale do Rio dos Sinos, 2008)
The goal of this research is to establish a relation between the concepts of family and work by analyzing the childhood during the first years of the industrialization process in Caxias do Sul. The analysis starts with private contracts of apprentices, and then some life trajectories have been constructed. By means of spoken reports, the notion of childhood in the region has been identified, and from state public documentation, assistance initiatives to children have been mapped, as well as the policy to manpower formation. The theoretical-methodological referential was the social history of work, family and childhood.
Keywords: Infância; Trabalho infantil; Família; Industrialização; Childhood; Child labor; Family; Industrialization; ACCNPQ::Ciências Humanas::História